Robust cooperative tracking protocol design for networked higher order nonlinear systems via adaptive second order sliding mode - Khan, Qudrat; Akmeliawati, Rini (IEEE, 2018)
A distributed synchronization protocol design for networked higher order nonlinear systems (NHONS) is focused this work. The nodes in the network are supposed to communicate via a predefined network topology. One of the nodes (also called agents) is considered as a leader while the remaining agents are treated as followers. Assuming that the motion equations of the agents are known during the whole process. A synchronization error based generalized higher order nonlinear uncertain dynamic system is defined, which takes into account the perturbed dynamics of all the agent. The proposed law incorporate equivalent control and the super twisting control. This design successfully nullifies the effects of the uncertainties and confirms a robust finite time second order sliding mode control(SOSMC) enforcement with suppressed chattering and reduced stress . Having established the sliding mode against the manifold of networked synchronization errors, an asymptotic synchronization is achieved which is an appealing applications of higher order sliding modes. A simulation example is presented to demonstrate this strategy.